Association studies of calcium-sensing receptor (CaSR) polymorphisms with serum concentrations of glucose and phosphate, and vascular calcification in renal transplant recipients. - Valerie N Babinsky; Fadil M Hannan; Sonia C Youhanna; Céline Maréchal; Michel Jadoul; Olivier Devuyst; Rajesh V Thakker (PLoS ONE)
Background Cardiovascular disease is the major cause of death in renal transplant recipients (RTRs) and linked to arterial calcification. The calcium-sensing receptor (CaSR), a G-protein coupled receptor, plays a pivotal role in extracellular calcium homeostasis and is expressed in the intimal and medial layers of the arterial wall. We investigated whether common CASR gene variants are predictors for aortic and coronary artery calcification or influence risk factors such as serum calcium, phosphate and glucose concentrations in RTRs. Methods Two hundred and eighty four RTRs were investigated for associations between three CASR promoter region single nucleotide polymorphisms (SNPs) (rs115759455, rs7652589, rs1501899), three non-synonymous CASR coding region SNPs (A986S, R990G, Q1011E), and aortic and coronary artery calcium mass scores, cardiovascular outcomes and calcification risk factors that included serum phosphate, calcium, total cholesterol and glucose concentrations. Results Multivariate analysis revealed that RTRs homozygous for the minor allele (SS) of the A986S SNP, when compared to those homozygous for the major allele (AA), had raised serum glucose concentrations (8.7±5.4 vs. 5.7±2.1 mmol/L, P<0.05). In addition, RTRs who were heterozygous (CT) at the rs115759455 SNP, when compared to those homozygous for the major allele (CC), had higher serum phosphate concentrations (1.1±0.3 vs. 1.0±0.2 mmol/L, P<0.05). CASR SNPs were not significant determinants for aortic or coronary artery calcification, and were not associated with cardiovascular outcomes or mortality in this RTR cohort. Conclusions Common CASR SNPs may be independent predictors of serum glucose and phosphate concentrations, but are not determinants of vascular calcification or cardiovascular outcomes.